2017
DOI: 10.1097/mpa.0000000000000911
|View full text |Cite
|
Sign up to set email alerts
|

Is Multifocality an Indicator of Aggressive Behavior in Small Bowel Neuroendocrine Tumors?

Abstract: Objectives Many patients with small bowel neuroendocrine tumors (SBNETs) have multifocal tumors (MFTs), but the frequency of MFTs has varied widely across SBNET studies. It is also unclear whether patients with MFTs have more advanced disease or worse clinical course than those with unifocal SBNETs (UFTs). We set out to determine the frequency of multifocal and unifocal SBNETs, compare clinicopathologic factors, somatostatin receptor (SSTR2) expression, and survival. Methods Clinicopathologic variables from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
41
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(49 citation statements)
references
References 30 publications
6
41
2
Order By: Relevance
“…studied 68 SI‐NET patients (50 with unifocal and 18 with multifocal disease), concluding that multifocal disease occurred in younger patients (in contrast to findings in our study) and conferred a worse prognosis on multivariate, stage‐adjusted analysis . In contrast, two other more recent and larger series of SI‐NETs are concordant with our findings that tumour focality has no bearing on SI‐NET recurrence or prognosis . (It should be noted that our high proportion of grade 1 SI‐NETs, relatively short follow‐up and relatively few deaths from disease in our cohort make it difficult to assert that unifocal and multifocal disease have different prognoses based solely on our findings.)…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…studied 68 SI‐NET patients (50 with unifocal and 18 with multifocal disease), concluding that multifocal disease occurred in younger patients (in contrast to findings in our study) and conferred a worse prognosis on multivariate, stage‐adjusted analysis . In contrast, two other more recent and larger series of SI‐NETs are concordant with our findings that tumour focality has no bearing on SI‐NET recurrence or prognosis . (It should be noted that our high proportion of grade 1 SI‐NETs, relatively short follow‐up and relatively few deaths from disease in our cohort make it difficult to assert that unifocal and multifocal disease have different prognoses based solely on our findings.)…”
Section: Discussionsupporting
confidence: 88%
“…(It should be noted that our high proportion of grade 1 SI‐NETs, relatively short follow‐up and relatively few deaths from disease in our cohort make it difficult to assert that unifocal and multifocal disease have different prognoses based solely on our findings.) The former, but not the latter, study also found a higher rate of nodal metastasis in multifocal SI‐NETs.…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations